Czym jest neomediewalizm? (Politeja, 2019)
What Is Neomedievalism?The article has a purpose to present the theory of neomedievalism. This theory has been developed in order to explain changes in today’s world by using analogy to the social system that existed in the pre-nation state era. The main focus of the theory of neomedievalism is the system of multiple, self constructed loyalties that can work simultaneously without one being superior to others. Neomedievalism focuses on the idea that the era of post-Westphalian nation states is over and it has been replaced by a more globalized system that is based on multiple loyalties. This article presents the basic ideas and indicators of the existence of neomedievalism. The indicators of neomedievalism are presented mostly on the example of African continent after the end of the colonial times.